Gravitational study of escape routes and residence regions of Ceres and Vesta fragments - Zain, Patricio Salvador (2023)
Aims. Ceres and Vesta are the two largest bodies in the main asteroid belt (MB) and have been extensively studied, particularly sincethe DAWN mission. Vesta is known to have an associated asteroid family, while the existence of a Ceres family is uncertain. Thisstudy investigates the fate of multi-kilometre fragments ejected from Ceres and Vesta due to impacts over a timescale of severalhundred million years.Methods. We performed purely gravitational N-body simulations to investigate the dynamical evolution of multi-kilometre-sizedfragments ejected from Ceres and Vesta. We tracked the trajectories of these fragments and identified their residence regions withinthe MB. We analysed the escape routes and end states of the fragments that manage to leave the MB, including the delivery to thenear-Earth asteroids (NEAs). We also estimated the number of collisions with Earth that could be attributed to large fragments ejectedfrom Ceres and Vesta.Results. Our simulations show that the Ceres fragments are dispersed over a larger region in the MB compared to Vesta fragments dueto their higher ejection velocities. We identified the escape routes of the fragments that leave the MB, which for the Ceres fragmentsare the 5:2 and 8:3 mean-motion resonances (MMR), and for the Vesta fragments are the 3:1 MMR and ν6 secular resonance, wherethey can be delivered to the NEA region. We also find that the Pristine region, located between the 5:2 and 7:3 MMR, is the mostlikely place to find any surviving member of a Ceres family. There were no collisions of large Ceres or Vesta fragments with Earthover the age of the Solar System, suggesting that, under the model considered here, the howardite–eucrite–diogenite (HED) meteoritesoriginate from smaller NEAs from Vesta.